Қазіргі заманғы философиядағы ақпараттық кеңістік ұғымын зерттеу ерекшеліктері - Balabekuly, D.; Abdullah, K.; Altaev, Zh. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
Social-philosophy is looking for answers to many contemporary issues. There are many changes in the world. One state in the face of development, while other state is collapsing. Despite that fact, there are still developing countries. As the state develops, different issues will arise. The main development of the society is a time indicator. Moreover, the concept of time and space is parallel. Therefore, existences in space and relationship form an informational environment. There is a common problem of modern information space. The world’s people live in an informational space without borders. After all, the Internet has become a global network. Although, each country has its own information space, we find that a broader view of the information space has not been fully explored yet. Then, is the information space unlimited and at the global level? The information space is therefore the centerpiece of today’s information society. It is alarming that we use different types of TV and radio, cellular communications, virtual conversations with each other through social networking, and consciousness to digital technology. Information is updated at the every moment, not even in an every hour. Traditional media – this is losing for speedy media, that sends poor, fake information. This is also the current problem of information space in the media world. Therefore, the article provides the basic concepts of the systematic methodology of this information space and the methods used as tools to study the information space. Key words: information space, information society, information systematization, virtual communication.